2021
DOI: 10.3390/jcm10061200
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7)—A Potential Remedy for AKI: Insights Derived from the COVID-19 Pandemic

Abstract: Membrane-bound angiotensin converting enzyme (ACE) 2 serves as a receptor for the Sars-CoV-2 spike protein, permitting viral attachment to target host cells. The COVID-19 pandemic brought into light ACE2, its principal product angiotensin (Ang) 1-7, and the G protein-coupled receptor for the heptapeptide (MasR), which together form a still under-recognized arm of the renin–angiotensin system (RAS). This axis counteracts vasoconstriction, inflammation and fibrosis, generated by the more familiar deleterious arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 125 publications
0
21
0
Order By: Relevance
“…Furthermore, a reduction and/or inactivation of ACE2 caused by SARS-CoV-2 binding can increase the ACE/Angiotensin II signaling pathway and related pathologies [10]. Thus, the COVID-19 disease was shown to be characterized by ACE2 depletion, probably playing a key role in the devastating cytokine storm embodying this disorder [11].…”
Section: The Well-known Ace Role and Its Controversial Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a reduction and/or inactivation of ACE2 caused by SARS-CoV-2 binding can increase the ACE/Angiotensin II signaling pathway and related pathologies [10]. Thus, the COVID-19 disease was shown to be characterized by ACE2 depletion, probably playing a key role in the devastating cytokine storm embodying this disorder [11].…”
Section: The Well-known Ace Role and Its Controversial Involvementmentioning
confidence: 99%
“…Conversely, it was suggested that ACE2 has the potential of slowing the progression of experimental diabetic chronic kidney disease [11], and it was found to be highly and significantly expressed in the kidney among individuals with chronic kidney diseases or DN [12].…”
Section: The Well-known Ace Role and Its Controversial Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention should be drawn to the potential therapeutic approach based on restoration of the impaired RAAS balance during COVID-19 infection [130]. It is suggested that the cytokine storm and the coagulopathy during COVID-19 infection may be linked to the depletion of ACE2 and AG1-7, which, in the conditions of homeostasis, has a visible renoprotective impact [130]. Stimulation of the ACE2/AG1-7/MasR axis may be a potential target for COVID-19-associated AKI treatment.…”
Section: Management and Treatment Optionsmentioning
confidence: 99%
“…Autoantibodies have been identified in patients with coronavirus disease 2019 (COVID- 19), suggesting that the infection by severe acute respiratory syndrome virus 2 (SARS-CoV-2) can evolve to a systemic autoimmune disease [1][2][3][4][5] . For instance, high levels of antiphospholipid autoantibodies have been linked to severe respiratory disease by inducing neutrophil extracellular traps (NETs) and venous thrombosis 4,[6][7][8][9] .…”
Section: Mainmentioning
confidence: 99%